TRAINING OF MIDDLE-LEVEL PERSONNEL BASED ON THE NEEDS OF THE PRIVATE SECTOR IN THE LABOR MARKET: CHALLENGES AND SOLUTIONS (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article presents the socio-economic importance of training middle-level personnel based on the needs of the private sector in a market economy, as well as existing challenges and solutions.The results of the work carried out on the training of middle-level personnel based on the needs of employers in the private sector were analyzed, and recommendations were developed to improve the processes of training competitive middle-level personnel in the vocational education system.
Keywords: labor market, internal and external labor market, vocational training, career guidance, vocational education, vocational educational institutions, middle-level personnel, the need of the private sector, employers, jobs, new jobs, business entities, Chamber of Commerce, dual education.